Pharmaceutical Approval Update - Fellner, Chris (P T, 2016)
Emtricitabine/rilpivirine/tenofovir alafenamide (Odefsey) for combination HIV-1 therapy; dapsone gel, 7.5% (Aczone) for acne vulgaris; extended-release tofacitinib (Xeljanz XR) for rheumatoid arthritis; and brivaracetam (Briviact) for epilepsy